Hungarian Monitoring, 1 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Pravda article on circumstances surrounding outbreak of WWII - Strikes come to an end in Gdansk on Walesa's recommendation Domestic Affairs: - Károly Grósz speech on Miners' Day - Conference in Nádudvar on propaganda and information - Arad summit and reactions - Situation for Gypsies - Neo-Fascist phenomena Economy: - Modification of the tax law Külpolitika: - Pravda cikk a II. világháború kirobbanásának körülményeiről - Walesa javaslatára beszüntették a sztrájkot Gdanskban Belpolitika: - Grósz Károly beszéde a Bányász Napon - Nádudvari tanácskozás a propagandáról és a tájékoztatásról - Az aradi csúcs és visszhangja - Cigányság helyzete - Újfasiszta jelenségek Gazdaság: - Az adótörvény módosítása